Theoretical and experimental analysis of the effects of the series resistance on luminous efficacy in GaN-based light emitting diodes - 马莉 沈光地 刘建朋 高志远 徐晨 王勋 (Chinese physics B, 2014)
In this paper, a new equivalent circuit model of GaN-based light emitting diodes （LEDs） is established. The impact of the series resistance to luminous efficacy is simulated using the MATLAB software. GaN-based LEDs with different n- contact electrode materials （LEDs with Ni/Au and LEDs with Cr/Au） are fabricated. By comparing and analyzing the results of performances, we concluded that both the series resistance and the carrier loss could affect the luminous efficacy severely. LEDs with lower series resistance have higher luminous efficacy and its efficiency droop is alleviated simultaneously. To improve luminous efficacy, the fabrication process should be optimized for lower series resistance.